Peningkatan Keterampilan Penulisan Karya Ilmiah melalui Penggunaan Sitasi Mendeley - Bachrul Ulum; Aditya Pringga Satria; Leny Suryaning Astutik; Dwi Agustina Rahayu; Piping Rahadianto (Insan Kreasi Media, 2024)
This community service aims to enhance the academic writing skills of students, particularly those in the early semesters of college, through the utilization of article citations from national and international journals with the assistance of Mendeley. The community service method involves intensive training sessions on Mendeley for early semester students at Bhinneka PGRI University Tulungagung. This training consists of preparation, implementation, and evaluation stages. The results of the community service indicate that Mendeley training is effective in improving efficiency and accuracy in article citations as well as overall reference management skills. With this training, it is expected that students can produce quality academic papers with accurate and structured citation approaches.